Heart rate variability as a transdiagnostic biomarker of psychopathology - Beauchaine, Theodore P.; Thayer, Julian F. (International journal of psychophysiology, 2015)
The Research Domain Criteria (RDoC), developed by the National Institute of Mental Health as a neuroscience-informed alternative to traditional psychiatric nosology, is an explicitly dimensional system in which classification of psychopathology is derived inductively (i.e., from basic science), across multiple levels of analysis (e.g., genetic, neural, psychophysiological, and behavioral). Although RDoC is often presented as paradigmatically revolutionary, a review of the history of psychophysiology suggests that roots of RDoC thinking extend at least as far back as the mid-20th Century. In this paper, we briefly and selectively review the historical emergence of neurobiologically-informed dimensional trait models of psychopathology, and we summarize our thinking regarding high frequency heart rate variability (HF-HRV) as a transdiagnostic biomarker of self-regulation and cognitive control. When functional interactions between HF-HRV and systems of behavioral approach and avoidance are considered, diverse patterns of behavioral maladjustment can be subsumed into a single model. This model accommodates the general bifactor structure of psychopathology, and suggests that HF-HRV can be viewed as an autonomic, transdiagnostic biomarker of mental illness. •RDoC is an inductive system of classifying psychopathology across levels of analysis.•In psychophysiology, RDoC thinking extends back to the mid-20th Century.•Heart rate variability (HRV) is a transdiagnostic biomarker of self-regulation.•HRV, combined with other biobehavioral systems, explains diversity of psychopathology.•This model accommodates the general bifactor structure of psychopathology.